2020
DOI: 10.1088/1475-7516/2020/03/042
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprint matching of beyond-WIMP dark matter: neural network approach

Abstract: Galactic-scale structure is of particular interest since it provides important clues to dark matter properties and its observation is improving. Weakly interacting massive particles (WIMPs) behave as cold dark matter on galactic scales, while beyond-WIMP candidates suppress galactic-scale structure formation. Suppression in the linear matter power spectrum has been conventionally characterized by a single parameter, the thermal warm dark matter mass. On the other hand, the shape of suppression depends on the u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 228 publications
(350 reference statements)
0
6
0
Order By: Relevance
“…Indeed, there has recently been considerable interest in how machine-learning techniques, such as the implementation of neural networks, can be applied to various aspects of early-universe cosmology. For example, emulators trained on Einstein-Boltzmann solvers have been used to generate estimates for observables such as the linear matter power spectrum and the CMB directly from either standard cosmological parameters [80][81][82][83][84] or the parameters associated with specific models [85]. Neural networks have also been used to eliminate computational bottlenecks involving the most time-intensive or least-parallelizable steps in the calculations performed by these solvers [86].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Indeed, there has recently been considerable interest in how machine-learning techniques, such as the implementation of neural networks, can be applied to various aspects of early-universe cosmology. For example, emulators trained on Einstein-Boltzmann solvers have been used to generate estimates for observables such as the linear matter power spectrum and the CMB directly from either standard cosmological parameters [80][81][82][83][84] or the parameters associated with specific models [85]. Neural networks have also been used to eliminate computational bottlenecks involving the most time-intensive or least-parallelizable steps in the calculations performed by these solvers [86].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…By equating the power spectra, the authors found a relation between these two scenarios, which possess distribution functions with the same analytical expression but with different parameters. A similar matching procedure using the mean square of the DM velocity was proposed in [70] and extended in [71,72] for several freeze-in models. As we show below, our (generalized) matching relation can be applied to a wide variety of NCDM scenarios, even for those in which thermal equilibrium is not established before DM decoupling.…”
Section: Analytical Rescaling and Generalized Phase Space Distributionmentioning
confidence: 99%
“…The first class comprises methods which are sensitive to the properties of the power spectrum only at relatively low values of k [7][8][9][10][11][12][13][14][15][16][17][18]. By contrast, the second class comprises methods which are sensitive to the properties of T (k) over a broader range of k [19][20][21][22][23][24][25][26][27][28][29]. We shall refer to recasts which fall into these two classes as "half-mode" and δA recasts, respectively.…”
Section: Introductionmentioning
confidence: 99%